Organização lito-estrutural do duplex Salobo-Mirim Serra dos Carajás - SIQUEIRA, José Batista (Universidade Federal do Pará, 2019)
The Salobo Group embodies a sequence of volcanosedimentary rocks, which overlain a sialic basement, and is linked to the evolution of the Cinzento Transcurrent System, situated immediately to the north of the transcurrent system which provided the estabelishment of the Grão-Pará Group. The macrostructure is formed by two major shear zones which join at the west and east end parts of the studied area, defining a WNW-ESE eliptcal structure. This structure, which is interpreted as an extensional duplex, comprises, internally, minor shear zones that converge to the main zones. NW-SE, NNE-SSW and NE-SW strike-slipe zones modify the major geometric pattern. The duplex lithologies underwent metamorphism of the amphibolite facies during regional transpression, followed by expressive hidrotermalism and greenschist facies transformation trought the progress of the deformation. Significant mineralizations of bornite, chalcocite and in some cases chalcopirite, with molibdenite, gold and silver, are mainly hosted by lenses of iron formations, besides magnetite. These sulphides are distrubuted as inclusions in the grains of silicate gangue minerals and oxides or between them, as well as along the ductile and ductile-ruptile features, such as milonitic S-C foliations and R, R', p and y=D fractures, showing the manifold origin of such mineralizing fluids. Two kinematics models can be visualized to explain the main litho-structural units: sinistral stike-slip system involving transtension, followed by transpression and then transtension; and crotonic reworking related to transtension regime.